Parents’ and Students’ Attitudes Toward Tablet Integration in Schools - Zhu, Sha; Yang, Harrison Hao; MacLeod, Jason; Shi, Yinghui; Wu, Di (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2018)
This study explored parents’ and students’ attitudes toward tablet usage in a formal educational setting. A total of 212 students from four 7th-grade classes, along with 145 of their parents, responded to the Tablet Acceptance Questionnaire. Quantitative methods including a t-test and partial least square (PLS) analyses were employed to examine students’ and parents’ attitudes toward tablet integration in schools, and to investigate factors influencing students’ and parents’ attitudes toward tablet usage, respectively. The results indicated significant differences between students’ and parents’ attitudes. Empirical findings suggested students hold more positive views than their parents with regard to tablet usage, tablet benefits for learning, and technical advantages and ease of use. Conversely, parents expressed greater concern over potential negative effects of tablet usage in education than do their children. This study also suggested educational benefits of tablet usage were the key factor influencing both students’ and parents’ attitudes. Based on the cross-examined understanding of parents’ and students’ attitudes, suggestions for large scale tablet initiatives are proposed.